Scale in education research: towards a multi-scale methodology - Noyes, Andrew (Taylor and Francis, 2013)
This article explores some theoretical and methodological problems concerned with scale in education research through a critique of a recent mixed-method project. The project was framed by scale metaphors drawn from the physical and earth sciences and I consider how recent thinking around scale, for example in ecosystems and human geography might offer helpful points and angles of view on the challenges of thinking spatially in education research. Working between the spatial metaphors of ecology scholars and the critiques of the human geographers, for example the hypercomplex social space in Lefebvre’s political-economic thinking and the fluid, simultaneous, multiple spatialities of Massey’s post-structuralism, I problematize space and scale in education research. Interweaving these geographical ideas with Giddens’ structuration and Bourdieu’s theory of practice, both of which employed what might be termed scale-bridging to challenge social science’s entrenched paradigms, leads me to reconsider what is possible and desirable in the study of education systems. Following the spatial turn in the social sciences generally, there is an outstanding need to theorise multi-scale methodology for education research.